Analysis physical workload, mental workload, and work stress on teachers at Public Special School of Surakarta - Pitaloka, Fitri Rahmawati Dyah; Widowati, Evi (Universitas Gadjah Mada, 2024)
Purpose: This study aimed to analyze the relationship between physical workload and mental workload towards work stress on special school teachers. In addition, it discovers the portrayal of the level of physical and mental workload and work stress. Methods: This study is a quantitative research through a cross-sectional approach. A total of 50 teachers was the sample. Variables in this study were physical workload, mental workload, and work stress. Data was collected with a pulse oximeter and questionnaires of NASA-TLX and PSS-10, and collected data was analyzed with the Spearman rank test. Results: The results of this study showed there is no relationship between physical workload and work stress. On the other hand, there is a relationship between mental workload and work stress (p-value=0.720; PR=0.762). Furthermore, 18% of teachers had a required improvement in physical workload, 12% had a very high mental workload, and 50% had moderate work stress (p-value=0.000; PR=0.552). Conclusions: This study indicated that there is no relationship between physical workload and work stress, in the other hand, there is a relationship between mental workload and work stress.